Features of Diseases of the Anterior Part of the Eye in Patients after COVID-19 - E. V. Yani; E. N. Orlova; K. E. Seliverstova (Oftalʹmologiâ, 2021)
There are quite systematic data of the ophthalmic manifestations in SARS-CoV-2, on the presence of conjunctivitis in patients with COVID-19, as well as on the detection of viruses in the lacrimal fluid and eye tissues. And, although ophthalmic manifestations are considered rather rare for COVID-19 and are not included in the list of important for diagnosis, there is not enough reliable data on the inflammatory processes of the eye’s anterior part and their connection with COVID-19, as well as those arising against the background of the treatment.Purpose. To study the development of inflammatory diseases of the anterior part of the eye in patients who have undergone the new coronavirus infection COVID-19.resu. In the Department of Infectious and Allergic Eye Diseases of the Helmholts National Medical Research Center of Eye Diseases, 88 patients with confirmed transferred new coronavirus infection COVID-19 of varying severity were observed. The main method of laboratory diagnostics is the detection of SARS-CoV-2 RNA in swabs from the nasopharynx, the patient’s sputum. Serodiagnostics of COVID-19 includes the determination of IgG-, IgM-antibodies to SARS-CoV-2 in the blood in an enzyme-linked immunosorbent assay.Results. Acute conjunctivitis associated with COVID-19 is quite rare and is an early sign of the disease. In the complex nonspecific topical therapy of viral conjunctivitis in COVID-19, along with etiopathogenetic systemic treatment, local eye medications with immunomodulatory and antiviral activity should be used. Conjunctivitis during a pandemic may be the only sign of COVID-19. The development of allergic conjunctivitis in COVID-19 is possibly associated not only with the effect of a viral agent, but also depends on the toxic effect of drugs used in the complex treatment of this disease. The increase in the number of patients with episcleritis after the postponed coronavirus infection needs further detailed study, with the analysis of laboratory data from this group of patients and the accumulation of clinical material.Conclusion. Ophthalmic manifestations in COVID-19 are very different, affecting various structures of the eye, occur at different periods — both during the course of the disease and after clinical recovery, and, of course, need further consideration, study and structuring.